2008
DOI: 10.1139/x08-020
|View full text |Cite
|
Sign up to set email alerts
|

Short-day treatment alters Douglas-fir seedling dehardening and transplant root proliferation at varying rhizosphere temperatures

Abstract: We tested effects of shortened day length during nursery culture on Douglas-fir ( Pseudotsuga menziesii var. menziesii (Mirb.) Franco) seedling development at dormancy release. Seedlings from a 42°N source were grown either under ambient photoperiods (long-day (LD)) or with a 28 day period of 9 h light : 15 h dark photoperiods (short-day (SD)). Seedlings were periodically removed from freezer storage from January to May. Sensitivity of plant tissues to cold temperatures was investigated via electrolyte leakage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…The intensity and duration of SD treatments vary widely across regions and nurseries, but typically fall within a range of 8-12 h of photoperiod for 14-35 days (Rosvall-Åhnebrink 1982; Konttinen et al 2003;Jacobs et al 2008;Luoranen et al 2009;MacDonald and Owens 2010;Fløistad and Granhus 2013). SD treatment promotes early growth cessation and induces bud set (Dormling et al 1968;Heide 1974;Ekberg et al 1979;Colombo et al 1989Colombo et al , 2001Fløistad and Granhus 2013), while also increasing seedling freezing tolerance (Dormling 1982;Colombo et al 1989Colombo et al , 2001Jacobs et al 2008). Thus, this cultural treatment is now regularly employed in container nurseries across Canada and Scandinavia in production of boreal conifers (Colombo et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The intensity and duration of SD treatments vary widely across regions and nurseries, but typically fall within a range of 8-12 h of photoperiod for 14-35 days (Rosvall-Åhnebrink 1982; Konttinen et al 2003;Jacobs et al 2008;Luoranen et al 2009;MacDonald and Owens 2010;Fløistad and Granhus 2013). SD treatment promotes early growth cessation and induces bud set (Dormling et al 1968;Heide 1974;Ekberg et al 1979;Colombo et al 1989Colombo et al , 2001Fløistad and Granhus 2013), while also increasing seedling freezing tolerance (Dormling 1982;Colombo et al 1989Colombo et al , 2001Jacobs et al 2008). Thus, this cultural treatment is now regularly employed in container nurseries across Canada and Scandinavia in production of boreal conifers (Colombo et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…menziesii (Mirb.) Franco (Luoranen et al 2007, Jacobs et al 2008, Fløistad & Granhus 2010. In our study, when seedlings were further reared in the nursery after short-day treatment and re-exposed to natural night length, short-day treated seedlings had greater height growth increment (0.9 cm) relative to natural day (0.1 cm).…”
Section: Photoperiod Treatment and Fall Fertilization Effects On Heigmentioning
confidence: 52%
“…However, studies conducted in mid-latitudes (30°-45° N) have proven that short-day treatments effectively altered seedling size and root growth capacity of transplants (Jacobs et al 2008, Kostopoulou et al 2011). These findings indicate that short-day cultural practices can also manipulate the quality of mid-latitude tree species.…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with this, Hawkins et al (1994) found SD treatment to promote photosynthesis and thereby provide carbohydrates for increased root development. Jacobs et al (2008) showed that SD treatment of Pseudotsuga menziesii (Mirb.) Franco seedlings (plug plants) led to increased root proliferation compared to control plants at 10 °C, while the opposite was the case at 20 °C.…”
Section: Introductionmentioning
confidence: 99%